Development of an effective biosorbent by fungal immobilization technique for removal of dyes - Alam, Md Zahangir; Khan, Mohammad Jakir; Kabbashi, Nassereldeen Ahmed; Abu Sayem, S. M. (Springer, 2018)
Charcoal activated carbon was modified through immobilization techniques on fungal biomass. Two fungal strains i.e. Aspergillus niger and Penicillium sp. were selected to immobilize the charcoal activated carbon on fungal biomass. The percentage of biomass production onto activated carbon was 88% for A. niger while it was 75% for Penicillum sp. The results of scanning electron microscope (SEM) showed clear changes between the external surfaces of charcoal activated carbon (AC) and activated carbon immobilized biomass (ACIB) which also indicated the formation of matrix onto AC by fungal mycelia. The ACIBs showed more functional groups as compared to the AC. The functional groups determined by the Fourier transform infrared spectroscopy (FTIR) for the ACIBs by A. niger and Penicillium sp. indicated various changes in achieving additional functional groups (phosphate ester, cyclic ether, alcoholic and phenolic groups) as compared to the AC. The results revealed that AC was morphologically modified by the immobilization techniques. Maximum adsorption capacity by ACIB of A. niger was achieved at a dosage of 15  mg/L for Reactive Black (98.2%), Congo Red (84.6%) and Malachite Green (82.6%) while 20 mg/L dosage was required for Methylene Blue to achieve highest decolorization (92.3%). The results of individual effect of ACIB, AC and biomass on the removal of reactive black 5 showed that maximum removal was obtained at 98.2, 88 and 75% respectively. The modified biosorbents as ACIBs developed by the A. niger and Penicillium sp. in an immobilized culturing process could be a potential agent for decolorization and removal of pollutants.